An Empirical Study on the Impact of Gen Z Investors' Financial Literacy to Invest in the Indian Stock Market - Nag, Amit Kumar; Shah, Janil (Indian Journal of Finance, 2022)
Purpose : The aim behind conducting this research was to identify the influence of financial literacy (FL) on the stock market investment decisions of individuals belonging to Gen Z in India. Attitude toward investment (AT) and perceived behavioral control (PBC) were considered as the mediating factors related to the same, while social factors (SF) and subjective norms (SN) were considered as independent factors. Design/Methodology/Approach : A Google form was used to collect primary data; 401 valid responses were considered for the present research work. G* Power 3.1.9.2 software was applied to determine the sample size. The research applied a non-probability convenient sampling technique for collecting the data through a questionnaire. Initially, convenience sampling was used, followed by snowball sampling. The questionnaire was distributed to our friends and acquaintances in five Indian states (Madhya Pradesh, Chhattisgarh, West Bengal, Gujarat, and Maharashtra). Then, friends and acquaintances were asked to circulate the same survey to their friends and acquaintances in their respective cities, and so on. This research used confirmatory composite analysis to observe linear compound interrelationships. The SmartPLS software was utilized in order to conduct an analysis of partial least square structural equation modeling. Findings : Financial literacy had the highest positive effect on investment intention (Î² = 0.435). AT and PBC, which are the mediating variables, had a total positive effect of (Î² = 0.403) and (Î² = 0.275) on investment intention, respectively. FL had a total positive effect of (Î² = 0.358) and (Î² = 0.614) on AT and PBC, respectively. SF had a total positive effect of (Î² = 0.118) on AT, and SN had a total positive effect of (Î² = 0.219) on investment intention. Originality Value : The current study will undoubtedly aid in the development of an understanding of the most critical aspects impacting the stock market investing intentions of Gen Z.